A Systematic Review of Empirical Evidence on Art Therapy With Traumatized Refugee Children and Youth - Annous, Nadia; Al-Hroub, Anies; El Zein, Farah (Frontiers in Psychology, 2022)
The present study is an attempt to evaluate evidence of empirical rigor by systematically reviewing intervention studies that examined the effectiveness of art therapy in the treatment of PTSD symptoms in refugees between 2010 and 2020. The CEC evidence-based practice (EBP) standards and quality indicators were used to evaluate the methodological soundness of the reviewed studies. Seventy (70) research articles were identified for screening through systematic database search; 8 articles met the inclusion criteria. Results indicated that, though considered a promising treatment approach, art therapy is presently classified as an intervention that falls under the category of practice with insufficient evidence. Further methodologically sound experimental studies are warranted to strengthen the evidence behind art therapy as an intervention to reduce PTSD symptoms in refugees around the world.